Optimasi Parameter Quenching dan Tempering pada HRP Steel Lokal sebagai Baja Armor Nasional - Yurianto, Yurianto; Soenoko, Rudy; Soeprapto, Wahyono (Jurnal Rekayasa Mesin, 2018)
Armor steel is a high strength and hardness steel that used to protect against damage by an object, individual or vehicle from the direct pressure of projectile. In Indonesia, this steel is made of hot rolled plate steel and heat treated by quench and temper, the result is Quenched & Tempered Steels used for military components (such as main battle tank and the like) and commercials (such as making heavy equipment and others) manufactures. The problems of this study can be formulated by â€œWhat are the optimum hardness number and toughness that can be achieved by HRP Steel made in Indonesia?â€. This study aims to find the optimum parameter of quenching and tempering heat treatment to the hardness and toughness of HRP Steel made in Indonesia. The method of this study to combining quench and temper heat treatment by optimizing austenitization temperature; holding time of austenitization; tempering temperature; holding time of tempering. Optimization is done by using Minitab 16 Software. The result of the study is austenitization temperature 900 oC; holding time of austenitization 45 minutes; tempering temperature 125 oC; holding time of tempering 45 minutes; hardness prediction 569,96 HVN (and hardness influenced by tempering). For austenitization temperature 900 oC; holding time of austenitization 45 minutes; tempering temperature 175 oC; holding time of tempering 45 minutes; prediction of toughness 30.50 J (and toughness influenced by tempering).